Assessment of Health Follow up and Weight Control for Women with Osteoporosis in Baqubah City - Manal Y. Mohammed; Hala S. Abdulwahed (Iraqi National Journal of Nursing Specialties, 2022)
Objective(s): assessment of the health follow up and weight control for women with osteoporosis and find out the relationship between their health follow up and weight control and their socio-demographic characteristics. Methodology: A descriptive study was conducted on women with osteoporosis for the period of September, 26th 2020 to Jun, 20th 2021. Non- probability (convenient) sample of (70) women with osteoporosis selected from (5) Private Clinics for Joints and Fractures in Baqubah City. A questionnaire was designed though extensive review of literatures and it consists of three parts: the first part includes women’s socio demographic characteristics, the second part includes items on women’s health follow up , and the third part includes items on women’s weight control. Interview technique was used for data collection. The reliability and validity of the questionnaire was determined through a pilot study and a panel of (9) experts. The data was analyzed through the use of descriptive and inferential statistical analysis approaches. Results: The results of the study show that the majority of the study sample are within the age group of (40-49) years , married and housewives, low educated, with low family monthly income, and living in the rural area. most of these women are between fair level and a good level of health follow-up and fair level of weight control. Conclusions: The study concluded that women of osteoporosis need to be more complied with health follow up and weight control. Age is the only trait of women’s demographic characteristics that has a relationship with their health follow up and weight control. Recommendations: The study recommend for the conduction of Health education programs about weight control to presented for women with osteoporosis , and mass media can play an essential role in raising women’s awareness about health follow up and weight control.